1996
DOI: 10.1107/s0108767396076398
|View full text |Cite
|
Sign up to set email alerts
|

A new serine protease fold revealed by the crystal structure of human cytomegalovirus protease

Abstract: A new polypeptide backbone fold for serine proteases has been identified based on the crystal structure ofhmnan cytomcgalovi.J.us protease. The structure was detem1ined at 2.5A resolution by the multiplewavelength anomalous diJ'fraction technique using the seleno-methionyl protein and refined at 2.0A resolution. It reveals a seven-stnmded mostly-antipm·allel 13-ban·eL which is sunounded by seven helices. The active site residues (Ser-132 and His-63) m·e situated on the outside of the 13-bmrel and in a groove o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…The Ser/His/His catalytic triad was validated by the crystal structure of the cytomegalovirus protease (Qiu et al 1996;Shieh et al 1996;Tong et al 1996). The structure revealed that the protein has a unique fold with the Ser132 Og atom and bridging His63 Ne2 nitrogen being within hydrogen-bonding distance (Fig.…”
Section: Ser/his/his Triad: Cytomegalovirus Proteasementioning
confidence: 99%
“…The Ser/His/His catalytic triad was validated by the crystal structure of the cytomegalovirus protease (Qiu et al 1996;Shieh et al 1996;Tong et al 1996). The structure revealed that the protein has a unique fold with the Ser132 Og atom and bridging His63 Ne2 nitrogen being within hydrogen-bonding distance (Fig.…”
Section: Ser/his/his Triad: Cytomegalovirus Proteasementioning
confidence: 99%
“…Each subunit of this protease contains a catalytic triad that maintains a similar geometry as seen for other serine proteases. On the other hand, each subunit is a single domain a/P protein and processes a different overall fold from other members of the serine protease family (Chen et al, 1996;Qiu et al, 1996;Shieh et al, 1996;Tong et al, 1996).…”
Section: Overall Three-dimensional Structurementioning
confidence: 99%
“…2) [58,59]. The stabilization of the oxyanion hole is realized in a similar manner in all serine proteases as well.…”
Section: Assemblinsmentioning
confidence: 69%
“…The first crystal structures of an assemblin were published by three groups in 1996 [58,59,83]. All three structures are of dimeric HCMV-assemblin.…”
Section: Structurementioning
confidence: 99%